Desafios regulatórios do Banco Central do Brasil diante das evoluções tecnológicas das empresas financeiras “fintechs” no século XXI - Ferreira, Glauber (2018)
The focus on the dissertation will be to examine the actions taken by the regulatory body of the National Financial System, the central bank of Brazil in face of the technological innovations that cross the financial sector in the 21st century. To achieve it, a diagnosis is made of the impacts caused by Fintechs in the financial market and the regulator’s perceptions about positive factors and the new sources of uncertainties or challenges that can affect financial stability. Regarding to the new scenario, this paper aims to contribute to the discussion about central bank’s roles which is the main monetary authorities of the country with the function of basing the role of regulating the financial system, avoiding that market failures appear with the changes originated by the new financial ecosystem. In order to unveil the challenges of the Brazilian central bank into the face of the disruptive movement, the actions taken by the international regulatory agencies and the first action taken internally by the central bank’s technological movements of the main centers for the propagation of financial products and services through the platforms electronic credit or named Fintechs Credit. It is concluded that the actions taken so far, BC of Brazil has been acting prudently and conservatively ways regarding to the new rearrangement due to nowadays, this issues are in tremendous boom in the financial market and any regulatory movement created that improved efficiency, could end up some technological changes in the financial sector and "scratching" the credibility of Brazil's central bank.